1986
DOI: 10.1029/jc091ic02p02372
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic transfer of simulated altimeter data into subsurface information by a numerical ocean model

Abstract: A global, eddy‐resolving capability to predict the ocean circulation is technologically feasible within the next decade. For this purpose, the satellite altimeter is the most promising operational source of oceanic data with global coverage, but only at the surface. A comparable source of subsurface data is not on the horizon. This investigation demonstrates the ability of a numerical ocean model to dynamically transfer simulated altimeter data into subsurface information. This was done for a variety of dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(53 citation statements)
references
References 49 publications
1
52
0
Order By: Relevance
“…For example, a two-layer model for investigating the Table 1. Kuroshio current, by Isobe and Imawaki (2002) used parameters of h 1 = 600 m, h 2 = 2400 m, and ε = 0.0020, and give a deviation factor of 0.99984. Parameters found in other several two-layer models on western boundary currents (Hurlburt, 1986;Yoon and Yasuda, 1987;Endoh and Hibiya, 2000) give a deviation factor 0.99981-0.99990, being a 0.01-0.02% deviation from √ g(h 1 + h 2 ). Therefore, the delay of the distant tsunami propagation behind √ g H (0.8-1.0% deviation) arises mostly from the SAL effect, and weakly from ocean density stratification.…”
Section: Discussion On the Optimal β βmentioning
confidence: 99%
“…For example, a two-layer model for investigating the Table 1. Kuroshio current, by Isobe and Imawaki (2002) used parameters of h 1 = 600 m, h 2 = 2400 m, and ε = 0.0020, and give a deviation factor of 0.99984. Parameters found in other several two-layer models on western boundary currents (Hurlburt, 1986;Yoon and Yasuda, 1987;Endoh and Hibiya, 2000) give a deviation factor 0.99981-0.99990, being a 0.01-0.02% deviation from √ g(h 1 + h 2 ). Therefore, the delay of the distant tsunami propagation behind √ g H (0.8-1.0% deviation) arises mostly from the SAL effect, and weakly from ocean density stratification.…”
Section: Discussion On the Optimal β βmentioning
confidence: 99%
“…Thus, the topographic waves are not continually captured by the Geosat. The GS and the NAC with H 1 = 250 m are only marginally unstable for a meander with L w = 220 km, while such a meander rapidly grows with H 1 = 500 m. Assimilation for 220-km wavelength meanders may not be feasible using the model with the 500-m thick upper layer, because the repeat cycle interval of 17 days is longer than the e-folding time scale of 10 days (Hurlburt, 1986).…”
Section: Basic Examination Of Model Behaviormentioning
confidence: 99%
“…Hurlburt (1986) assimilated "simulated" altimeter data only as sea surface height information into a free surface, two-layer primitive equation model. He showed that the subsurface mesoscale field was reconstructed reasonably well by the mode adjustment, provided that update intervals were about half the shortest major time scale.…”
Section: Introductionmentioning
confidence: 99%
“…Initial evidence that the altimeter data could be effectively assimilated into models came mainly from idealised experiments using simple models (Hurlburt 1986) statistics on vertical structure (De Mey & Robinson 1987) and ideas on conservation of water mass properties (Cooper & Haines 1996).…”
Section: Modelling and Computational Capacitiesmentioning
confidence: 99%